Perspectives on additives for polymers. 1. Aspects of stabilization. Issue 1 (23rd November 2020) - Allen, Norman S.; Edge, Michele
Abstract: Since the earliest discovery and subsequent developments in the world of polymers associated problems and increasing applications have resulted in the rapidly expanding field of "additives." In this context, the term additive is very generalized in that it encompasses many facets associated with ever growing needs. Of the most important are antioxidants (primary and secondary), light stabilizers, processing aids, metal deactivators, flame retardants, biocides, nucleating agents, antistatic compounds, fillers, dyes, pigments (nano, micro, and macro) to name but only a few each serving a particular function and not necessarily all at the same time in the one package. This article presents a general perspective on the type, mode of action, properties, uses, and problems (and circumvention) based on some of the more important key additives. The properties and behavior of many additives in this regard relates very much to the initial incorporation and formulation and in turn is often a major controlling factor in end use performance from a physical, esthetic, structural, mechanical, and chemical point of view. Indeed, with many polymers like PVC, for example, one enters a highly complex world of interactions which can in many cases destroy or even enhance the activity of functional processing additives. Some of these will be highlighted and hopefully the aim being here to enthuse the polymer and additive manufacturers and technologists in the processing laboratories to become more aware of potential issues and problems. Abstract : Since the earliest discovery and subsequent developments in the world of polymers associated problems and increasing applications have resulted in the rapidly expanding field of "additives." In this context, the term additive is very generalized in that it encompasses many facets associated with ever growing needs. Of the most important are antioxidants (primary and secondary), light stabilizers, processing aids, metal deactivators, flame retardants, biocides, nucleating agents, antistatic compounds, fillers, dyes, pigments (nano, micro and macro) to name but only a few each serving a particular function and not necessarily all at the same time in the one package. This article presents a general perspective on the type, mode of action, properties, uses, and problems (and circumvention) based on some of the more important key additives. The properties and behavior of many additives in this regard relates very much to the initial incorporation and formulation and in turn is often a major controlling factor in end use performance from a physical, esthetic, structural, mechanical, and chemical point of view. Indeed, with many polymers like PVC, for example, one enters a highly complex world of interactions, which can in many cases destroy or even enhance the activity of functional processing additives. Some of these will be highlighted and hopefully the aim being here to enthuse the polymer and additive manufacturers and technologists in the processing laboratories to become more aware of potential issues and problems.